PA2 Satisfaction with information received: perceptions of the patient and the informal caregiver. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Dawber, R; Armour, K; Carter, C; Ferry, P; Meystre, C
Abstract : Background: Provision of information to patients and families is a priority of palliative care. Lack of information on symptoms, treatment and disease progress adversely affects patients' and caregivers' abilities to self manage and participate in decision making and care. Qualitative reports of end of life care suggest caregivers seek more information than patients. Ignorance of this need may hamper health promotion strategies and limitation of patient and caregiver morbidity during end of life and bereavement processes. Aim: To compare satisfaction of dying patients with information given; to proxy satisfaction estimates on the patient's behalf. Methods: Prospective study comparing assessment of satisfaction with information received by nurse, informal caregiver and dying patient (>64 years) in hospital. Assessments made within 24 h, using patient and caregiver versions of the palliative outcome scale (POS). Statistical analysis: weighted kappa for agreement between proxy and patient. Results: Informal caregivers overestimate dissatisfaction with level of information given compared to patients. Weighted kappa patient versus ICG 0.187 (slight agreement), n = 50. Conclusion: The disparity between patient and proxy information satisfaction reflects the complexity of participatory strategies to limit morbidity at the end of life. Proxy over- estimation of patient dissatisfaction with information received may reflect the caregivers own dissatisfaction. As death approaches, caregivers require more information than patients, their burden increases and they become the interpreter of patient symptoms. Ignorance may lead to overestimation of symptoms, early breakdown of social care, and unplanned admission, risking death other than in the patients preferred place. Meeting caregiver information needs may reduce caregiver burden and improve proxy assessments, reducing patient and caregiver morbidity.